Elementy autobiograficzne w zbiorze wywiadów "Gli antipatici" Oriany Fallaci = Autobiographical elements in the collection of interviews by Oriana Fallaci, "Gli antipatici" - Tichoniuk-Wawrowicz, Ewa (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Oriana Fallaci - "journalist, agitator, legend" - persistently built her own legend during decades of intensive journalistic and then literary work. Santo L. Arico considered her and all her work to be steeped not even in self-centeredness but in narcissism. So, is it possible to find traces of Fallacian autocreation and autobiographical elements in her interviews, focused though on meeting with other people?
Keywords: Fallaci, Oriana (1929-2006); wywiad; elementy autobiograficzne; podmiot autobiograficzny; autokreacja; interview; autobiographical elements; autobiographical subject; autocreation